Targeting autophagy: polydatin’s role in inducing cell death in AML - Fu, Ping; Luo, Qing; Wang, Chao; Chen, Liping; Dong, Chang; Yang, Ke; Wu, Guang (Frontiers in Pharmacology, 2024)
Acute myeloid leukemia (AML), a malignant disorder of the hematopoietic system, arises from leukemic stem cells (LSCs) and is the most prevalent form of blood cancer in adults. This study aimed to evaluate the therapeutic potential of polydatin (PD) in AML through ex vivo and in vivo studies, respectively. This study was prompted by PD’s novel role in enhancing tumor apoptosis and modulating autophagy. In vitro studies were conducted using the PD-responsive AML cell line KASUMI-1 and found that PD was able to suppress cell proliferation and induce apoptosis by regulating the autophagy pathway. Subsequently, molecular docking was employed to predict the interaction between PD and Autophagy-related protein 5 (ATG5), a key regulator in the autophagy pathway. It was observed that PD inhibited the ubiquitination of ATG5 and enhanced its protein stability, leading to an increase in ATG5 protein levels and subsequent activation of the autophagy pathway (see in Abstract Graphed). The effectiveness and safety of PD in treating AML were confirmed through in vivo experiments using a mouse transplant tumor model, yielding definitive results. Collectively, these results suggest that PD is a promising candidate for the early therapeutic intervention of AML, with a strong potential for clinical application.